An Analysis of Grade XI Students’ Errors in Solving Statistical Problems Based on Newman Error Analysis (NEA) Theory - Atiqa Firdaus; Subanji Subanji; Mochammad Hafiizh (Universitas Suryakancana, 2026)
This study aims to analyze the mistakes of grade XI students in solving statistical problems based on the Newman Error Analysis (NEA) stages. The research method used is qualitative descriptive with the research subjects of 30 high school students in Praya for the 2025/2026 school year. Data were collected through descriptive tests, interviews, and documentation, then analyzed using the Miles and Huberman model through the stages of reduction, presentation and drawing of conclusions. The results showed that students still made mistakes at almost all stages of Newman, including: reading errors (0.64%), comprehension errors (22.29%), transformation errors (26.75%), process skills errors (23.56%), and encoding errors (26.75%). The most mistakes occur in the transformation and writing stages, while the least mistakes occur in the reading stage. Factors that cause student errors include lack of understanding of concepts, mistakes in choosing formulas, inaccuracy in calculations, and the habit of not writing conclusions. The results of this study are expected to be a guideline for teachers in developing more efficient learning strategies to reduce student errors in statistical materials.